Classical themes : level 1 : favorite orchestral works arranged for piano solo by Fred Kern, Phillip Keveren and Mona Rejino - Kreader, Barbara; Kern, Fred.; Keveren, Phillip; Rejino, Mona.; Owell, Margaret (Milwaukee, Wis : Hal Leonard Corporation, 2003)
Includes : Air/Handel, Can-can/Offenbach, Morning/Grieg, Russian dance/Tchailkovsky, Trumpet voluntary/Clarke, Symphony no. 3/Beethoven.
Keywords: Piano music -- Methodology. -- Piano music -- Methodology -- Juvenile literature. -- Piano music -- Study and teaching